Tracers for Cardiac Imaging: Targeting the Future of Viable Myocardium - Carmela Nappi; Mariarosaria Panico; Maria Falzarano; Carlo Vallone; Andrea Ponsiglione; Paolo Cutillo; Emilia Zampella; Mario Petretta; Alberto Cuocolo (Pharmaceutics, 2023)
Ischemic heart disease is the leading cause of mortality worldwide. In this context, myocardial viability is defined as the amount of myocardium that, despite contractile dysfunction, maintains metabolic and electrical function, having the potential for functional enhancement upon revascularization. Recent advances have improved methods to detect myocardial viability. The current paper summarizes the pathophysiological basis of the current methods used to detect myocardial viability in light of the advancements in the development of new radiotracers for cardiac imaging.